SOSIALISASI KEGIATAN SURVEI INVESTIGASI DESAIN OPTIMASI LAHAN PADA PETANI PADI SAWAH DI DESA MUKTI JAYA KECAMATAN RIMBA MELINTANG ROKAN HILIR - Dewi, Novia; Arifudin, Arifudin; Bakce, Djaimi; Hadi, Syaiful; Hutabarat, Sakti; Rifai, Ahmad; Mustaqim, Mustaqim; Herlon, Meki; Ridho, Zulhamid; Yusmini, Yusmini; Khaswarina, Shorea; Mubarak, Mubarak; Andrina, Hanifaturrahmi (JP2N : Jurnal Pengembangan Dan Pengabdian Nusantara, 2025)
The Design Investigation Survey (SID) activity is a program by the Ministry of Agriculture aimed at utilizing swamp land to enhance food production through land optimization. The target location for land optimization in Rokan Hilir Regency is situated in Mukti Jaya Village, Rimba Melintang District. This community service activity aims to provide knowledge and guidance regarding the SID land optimization program to rice farmers in Mukti Jaya Village. This activity is beneficial for aligning perceptions regarding the requirements that serve as a reference for the SID land optimization activities, the necessary data, and the forms of assistance provided to improve land productivity and rice planting indices. The methodology involves outreach and guidance directed at the target  farmer groups. Outreach will cover the requirements and supporting data necessary for SID land optimization. Guidance will consist of directions regarding the infrastructure to be developed for optimizing land and its budgeting. There is a priority scale and budget provisions that will serve as a reference for communicating urgent needs in the field. The results of this community service activity indicate that (a) participants understand the importance of the SID land optimization program and its benefits for farmers, and (b) participants are aware of the criteria, requirements, and implementation provisions of the SID OPLA program from the Ministry of Agriculture, as well as the data that farmer groups need to provide.